Analyzing Similarities between the European Union Countries in terms of the Level of Digital Business Maturity - Magdalena TUTAK (Communications of International Proceedings, 2021)
Digital transformation of production and service enterprises has become a common direction of development for all economic sectors. The very idea of Industry 4.0 has become synonymous with innovation and the basis for business development. The role and importance of these transformations are also recognized by the EU, which for many years has been promoting and supporting the development of the digital economy. However, individual EU countries differ in terms of digital business maturity due to the implementation of Industry 4.0 technology. The paper addresses this issue by presenting the results of the research aimed at analyzing similarities between the EU countries in terms of the level of digital business maturity. The research was conducted using the k-means clustering method. The similarity analysis of the EU countries was performed using 8 determinants characterizing digital business maturity in relation to the applied technologies. The results indicate a high differentiation of the EU countries in this development. The leaders in terms of digital business maturity are undoubtedly Scandinavian countries (Finland, Sweden, Denmark) and only three countries from Western Europe (Belgium, the Netherlands and Ireland). Countries with the least favorable results in terms of digital business maturity include Greece, Romania, Bulgaria, Hungary, Latvia, Poland, and Cyprus. The findings provide a lot of new information about the current state of development of the digital economy in the EU countries, which should be used in both the development and implementation of new solutions related to the policy of economic digitalization in this region.
Keywords: Digital Maturity; Industry 4.0; Enterprises; European Union Countries.